2016
DOI: 10.1002/ecs2.1456
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating redispersal microsites into myrmecochory in eastern North American forests

Abstract: Studies addressing the benefits of "directed dispersal" in ant seed dispersal systems have highlighted the beneficial soil properties of the nests of ants that disperse their seeds. No studies, however, have explored the properties of soils nearby exemplary seed-dispersing ant nests, where recent work indicates that seeds are quickly "redispersed" in eastern North America. To address this, we focused on a forested ecosystem in eastern United States where a keystone seed-dispersing ant, Aphaenogaster rudis, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The main benefits attributed to redispersal are the further displacement of seeds from the parent plant (distance dispersal) and the reduction of inter- and intra-specific competition that is experienced on the nest middens. Such a reduction in seed aggregation is mainly effective if redispersed seeds are scattered to various locations, either randomly [ 29 , 62 ] or even non-randomly, as long as the resulting densities are lower than those prior to redispersal [ 23 ]. The non-random redispersal of S. clusiana seeds to shrub patches that we observed in our study often reduces intraspecific competition, as seeds from each C. savignyi colony were redispersed to 1–5 shrubs located at least a few meters from each other ( Figure A1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main benefits attributed to redispersal are the further displacement of seeds from the parent plant (distance dispersal) and the reduction of inter- and intra-specific competition that is experienced on the nest middens. Such a reduction in seed aggregation is mainly effective if redispersed seeds are scattered to various locations, either randomly [ 29 , 62 ] or even non-randomly, as long as the resulting densities are lower than those prior to redispersal [ 23 ]. The non-random redispersal of S. clusiana seeds to shrub patches that we observed in our study often reduces intraspecific competition, as seeds from each C. savignyi colony were redispersed to 1–5 shrubs located at least a few meters from each other ( Figure A1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ants may discard seeds in nest middens, or at sites some distance from nest entrances (Beattie 1985, Gorb and Gorb 2003, Canner et al 2012). This process is termed 're-dispersal' and is thought to represent an important stage of myrmecochory (Beaumont et al 2013, Warren and Giladi 2014, Connell et al 2016. While seed re-dispersal may reduce the probability that seeds obtain the benefits associated with being in a nest, it may under some circumstances reduce the negative density-dependence effects caused by seed aggregation in an ant nest (Spiegel and Nathan 2010, 2012, Warren and Giladi 2014.…”
Section: Introductionmentioning
confidence: 99%
“…While seed re-dispersal may reduce the probability that seeds obtain the benefits associated with being in a nest, it may under some circumstances reduce the negative density-dependence effects caused by seed aggregation in an ant nest (Spiegel and Nathan 2010, 2012, Warren and Giladi 2014. Thus, since not only the primary dispersal and the ant dispersal, but also the re-dispersal, might benefit myrmecochorous plants (Gorb and Gorb 2003, Bas et al 2009, Canner et al 2012, Beaumont et al 2013, Connell et al 2016, Bologna et al 2017, we need to evaluate the outcome of all steps in plants with diplochorous dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…This process, defined by the term ''seed re-dispersal'' is thought to represent an additional phase of myrmecochory (Gorb and Gorb 2003;C a n n e r et al. 2012;Beaumont et al 2013;Warren and Giladi 2014;Connell et al 2016). While seeds re-dispersed from nests may further increase dispersal distances away from the parent plant and reduce sib competition (Canner et al 2012), it may also re-expose seeds to predators like rodents and insects (Hughes and Westoby 1992;Lô bo et al 2011;Tanaka et al 2015).…”
Section: Introductionmentioning
confidence: 99%